2018
DOI: 10.1097/won.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pressure Injuries in a Critical Care Unit in Lebanon

Abstract: Vasopressor use, hypotension, and length of stay were associated with an increased likelihood of pressure injury in adults managed in an MSICU. None of these factors is specifically evaluated during completion of the Braden Scale for Pressure Sore Risk. Based on these findings we recommend development of a pressure injury scale specific to critically ill adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 36 publications
3
25
2
5
Order By: Relevance
“…6 In Europe, PI incidence among ICU patients is 8.10-31%. [7][8][9] Studies of Middle Eastern countries have shown that 8.90% of ICU patients developed PI during ICU stays in Iran, 10 followed by 17% in Turkey, 11 33.70% in Lebanon, 12 and 39.30% in Saudi Arabia. 13 Within China, ICU patients have the highest PI incidence, 4.48%, much higher than the overall PI incidence of 0.63%.…”
Section: Introductionmentioning
confidence: 99%
“…6 In Europe, PI incidence among ICU patients is 8.10-31%. [7][8][9] Studies of Middle Eastern countries have shown that 8.90% of ICU patients developed PI during ICU stays in Iran, 10 followed by 17% in Turkey, 11 33.70% in Lebanon, 12 and 39.30% in Saudi Arabia. 13 Within China, ICU patients have the highest PI incidence, 4.48%, much higher than the overall PI incidence of 0.63%.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure injuries (PIs) are a largely preventable healthcare problem in all areas of health care. Intensive care units (ICUs) are one of the care settings with a high incidence of PIs, with a prevalence ranging from 14%–33.7% (Coyer et al, ; El‐Marsi, Zein‐El‐Dine, Zein, Doumit, & Badr, ; Mehta, George, Mehta, & Wangmo, ). By contrast, the prevalence of PIs is 7.8%–13.5% in all clinical settings (Mehta et al, ; VanGilder, Lachenbruch, Algrim‐Boyle, & Meyer, ) and from 3%–18.5% in acute care settings (Coyer et al, ; Tubaishat, Papanikolaou, Anthony, & Habiballah, ; Whittington & Briones, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intensive care patients are at high risk of developing pressure injuries (PIs) because of their illness severity, vasopressor use, poor tissue perfusion, comorbidities immobility, mechanical ventilation, infrequent repositioning, and use of medical devices that come in contact with the skin and apply sustained tissue deformations . Common areas for PIs to develop include the sacrum, heels, mouth, ears, and nose .…”
Section: Introductionmentioning
confidence: 99%